2016
DOI: 10.1016/j.kint.2016.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Mice with mutant Inf2 show impaired podocyte and slit diaphragm integrity in response to protamine-induced kidney injury

Abstract: Mutations in the INF2 (inverted formin 2) gene, encoding a diaphanous formin family protein that regulates actin cytoskeleton dynamics, cause human focal segmental glomerulosclerosis (FSGS). INF2 interacts directly with certain other mammalian diaphanous formin proteins (mDia) that function as RhoA effector molecules. FSGS-causing INF2 mutations impair these interactions and disrupt the ability of INF2 to regulate Rho/Dia-mediated actin dynamics in vitro. However, the precise mechanisms by which INF2 regulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 26 publications
5
52
0
Order By: Relevance
“…Most disease-associated inf2 mutations affect residues of the DID that are highly conserved across vertebrate INF2 homologs, and in some cases, even conserved in highly divergent invertebrate homologs, such as C. elegans INFT-2 ( Figure 5A). Pointing to a conserved role for INF2 in podocyte function, introduction into mice of the FSGSassociated inf2 mutation R218Q does not lead to kidney disease, but prevents their glomeruli from recovering from injury (Subramanian et al, 2016). Similarly, knockdown of inf2 in zebrafish results in several FSGS-like phenotypes that can be rescued by expression of wild-type inf2 mRNA, but not inf2 with the FSGS-associated mutations E184K or R218Q (Sun et al, 2014).…”
Section: Focal Segmental Glomerulosclerosis-a Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Most disease-associated inf2 mutations affect residues of the DID that are highly conserved across vertebrate INF2 homologs, and in some cases, even conserved in highly divergent invertebrate homologs, such as C. elegans INFT-2 ( Figure 5A). Pointing to a conserved role for INF2 in podocyte function, introduction into mice of the FSGSassociated inf2 mutation R218Q does not lead to kidney disease, but prevents their glomeruli from recovering from injury (Subramanian et al, 2016). Similarly, knockdown of inf2 in zebrafish results in several FSGS-like phenotypes that can be rescued by expression of wild-type inf2 mRNA, but not inf2 with the FSGS-associated mutations E184K or R218Q (Sun et al, 2014).…”
Section: Focal Segmental Glomerulosclerosis-a Kidney Injurymentioning
confidence: 99%
“…INF2 is expressed in podocytes, where it localizes in the foot processes to the slit diaphragms, and in a diffuse perinuclear pattern (Brown et al, 2010;Sun et al, 2011;Xie et al, 2015). INF2 colocalizes with other proteins important for slit diaphragm function, including nephrin, podocin, caveolin, mDia2, synaptopodin, and vimentin (Brown et al, 2010;Subramanian et al, 2016;Sun et al, 2011;Sun, Schl€ ondorff, Higgs, & Pollak, 2013;Tamura et al, 2016). In FSGS kidney samples, INF2 staining is reduced or absent (Tamura et al, 2016), and INF2 appears to be shed by podocytes into the urine in exosome-like vesicles in patients with kidney disease (Hogan et al, 2014).…”
Section: Focal Segmental Glomerulosclerosis-a Kidney Injurymentioning
confidence: 99%
“…FPE can occur within minutes, and is considered a protective response to preserve podocyte attachment under conditions of increased mechanical stress, such as during chronic kidney disease (reviewed in Kriz & Lemley, ). Notably, a number of INF2 mutations in humans can cause the kidney disease focal segmental glomerulosclerosis accompanied by FPE (Boyer et al, ; Brown et al, ), and a mouse INF2 mutant model shows an inability to reverse the transient FPE that occurs after induced acute kidney injury (Subramanian et al, ). INF2 is expressed in podocytes, and localizes in part to slit diaphragms, suggesting that the formin might contribute directly to the reversible plasticity of these junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Protein and fat droplets have also been observed in podocytes of obese Zucker rats (37), a model of diabetes from which the ZDF rats originate. Interestingly, a recent study observed granular localization of nephrin and podocin in a protamine sulfate–induced podocyte effacement model (38), suggesting that abnormal trafficking of nephrin, along with podocin, is not limited to diabetes. It may be that in situations requiring fast glomerular adaptation, such as in diabetes and protamine‐sulfate model, an increase in the turnover of the slit diaphragm proteins may lead to the saturation of the trafficking machinery, resulting in improper sorting and creation of aggregates containing nephrin and possibly other slit diaphragm components.…”
Section: Discussionmentioning
confidence: 99%